Low bit rate speech coding - Shah, Asadullah; Shaikh, Asadullah (IIUM Press, 2011)
In recent years much work has be concentrated on encoding speech. Various coding methods are developed such as Low-Delay Codebook Excited Linear Prediction (LD-CELP), Codebook Excited Linear Prediction (CELP), Pulse Residual Excited Linear Prediction (PRELP) and others. These encoders operate at very low bit rates (4.8Kbps) as well as maintained speech quality. In this chapter some ofthese encoding algorithms are explained